Care and protection of children on the street ages from 6 to 16 years in Djibouti-Ville - AHONNON, Adolphe; BIGA BOUKARY, Alassane; EDOH, KOFFI PIERROT (My University, 2019)
This study aims to contribute to appreciate the extent of the phenomenon of street children and their care. The study is qualitative of an analytical and critical nature. The research focused on 30 subjects in total, these subjects were chosen by the technique of reasoned choice. The research shows that the street becomes a field of intervention where many institutions are given the task of cleaning the street. In other words, many actors go through all the means to force these children to leave the street to return to the spaces of socialization. The results revealed that subjects perceive street children in three ways: offenders, victims and actors. In doing so, institutions prioritize family reintegration, integration or reintegration in to school and apprenticeship in a trade. The main purpose of these interventions is to get children to change their behavior so that they can regain their place in society.
Keywords: Street children; care; protection; reintegration